2005
DOI: 10.2165/00002018-200528050-00001
|View full text |Cite
|
Sign up to set email alerts
|

Potential Determinants of Drug-Drug Interaction Associated Dispensing in Community Pharmacies

Abstract: Although the number of clinically relevant drug-drug interactions (DDIs) is probably low, DDIs may be responsible for a substantial number of hospital admissions. In some countries, the pharmacist is responsible for preventing the use of unsafe or non-effective drug regimens. Specifically they should avoid the dispensing of combinations of drugs that may cause serious DDIs. In order to assess the determinants related to community pharmacies and associated with these dispensings, a systematic literature review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 19 publications
1
35
0
Order By: Relevance
“…The use of computer software for prospective medication surveillance is a very common approach to avoiding medication errors [1]. In our study, all community pharmacies were equipped with drug-interaction surveillance software, and most of them (90.2%) used it to identify potential drug interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of computer software for prospective medication surveillance is a very common approach to avoiding medication errors [1]. In our study, all community pharmacies were equipped with drug-interaction surveillance software, and most of them (90.2%) used it to identify potential drug interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Potential drug interactions are highly prevalent, but the number of adverse drug reactions caused by drug interactions is probably low [1][2][3][4]. Reported incidences in outpatients range from 9.2% to 70.3% for drug interactions of any severity, and from 1.2% to 23.3% for those considered of major relevance [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, pharmacies could be obliged to use medication surveillance screening programs, which is already the case in for example the Netherlands. 29 However, those programs will never be able to replace pharmacists' reasoning and decision making. Pharmacists, as drug experts, should take up their responsibility of detecting and preventing DRPs, if they wish to claim a role in DRP assessment.…”
Section: Discussionmentioning
confidence: 99%
“…74 A systematic literature review concluded that the number of prescribers, and the number of dispensing pharmacies, is important in determining the prevalence of clinically relevant drug-drug interactions. 75 An Australian study also found that having multiple prescribers increased patients' key medicationrelated risk factors and was associated with poor health outcomes. 76 Non-medical prescribing can lead to too many specialist health professionals, each prescribing medicines, without the oversight of a general practitioner.…”
Section: Issues With Expanded Roles For Pharmacistsmentioning
confidence: 99%